2008
DOI: 10.1093/aje/kwn079
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference and Mortality

Abstract: The authors examined the association between waist circumference and mortality among 154,776 men and 90,757 women aged 51-72 years at baseline (1996-1997) in the NIH-AARP Diet and Health Study. Additionally, the combined effects of waist circumference and body mass index (BMI; weight (kg)/height (m)(2)) were examined. All-cause mortality was assessed over 9 years of follow-up (1996-2005). After adjustment for BMI and other covariates, a large waist circumference (fifth quintile vs. second) was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
130
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 29 publications
16
130
0
8
Order By: Relevance
“…47,48 Regular physical activity and normal weight have been shown to be associated with a reduced risk of all-cause mortality, cardiovascular disease and cancer. 49 Increased fitness has been shown to have similar effects independently of body weight status, 50 further underlining the importance of the long-term health effects of habitual physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Regular physical activity and normal weight have been shown to be associated with a reduced risk of all-cause mortality, cardiovascular disease and cancer. 49 Increased fitness has been shown to have similar effects independently of body weight status, 50 further underlining the importance of the long-term health effects of habitual physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal obesity has been shown to be a risk factor for CVD and diabetes (Balkau et al, 2007a;Janiszewski et al, 2007). A large cohort study (Koster et al, 2008) showed that increased WC should be considered a risk factor for mortality, in addition to BMI. In our study, the prevalence of abdominal obesity in middle-aged women was obviously higher than that in young women.…”
Section: Discussionmentioning
confidence: 99%
“…Although usually highly correlated with BMI, there are data to suggest that waist circumference and/or WHR may predict health problems independently of BMI, as in diabetes mellitus (Gastaldelli, 2008) and CVD (Yusuf et al, 2005). Furthermore, there is accumulating evidence for a role of waist circumference (Visscher et al, 2001;Koster et al, 2008) and WHR (Lahmann et al, 2002;Price et al, 2006) in predicting mortality independently of BMI in men. A post hoc analysis of total PCa in the present cohort shows that the increased PCa risk associated with large waist circumference seemed to be greatest at low BMI (data not shown), a finding that was not explained by prevalent asymptomatic cancer.…”
Section: Discussionmentioning
confidence: 99%